Pharmacological rescue of trafficking-impaired ATP-sensitive potassium channels - Martin, Gregory M.; Chen, Pei-Chun; Devaraneni, Prasanna; Shyng, Show-Ling (Frontiers in Physiology, 2013)
ATP-sensitive potassium (KATP) channels link cell metabolism to membrane excitability and are involved in a wide range of physiological processes including hormone secretion, control of vascular tone, and protection of cardiac and neuronal cells against ischemic injuries. In pancreatic β-cells, KATP channels play a key role in glucose-stimulated insulin secretion, and gain or loss of channel function results in neonatal diabetes or congenital hyperinsulinism, respectively. The β-cell KATP channel is formed by co-assembly of four Kir6.2 inwardly rectifying potassium channel subunits encoded by KCNJ11 and four sulfonylurea receptor 1 subunits encoded by ABCC8. Many mutations in ABCC8 or KCNJ11 cause loss of channel function, thus congenital hyperinsulinism by hampering channel biogenesis and hence trafficking to the cell surface. The trafficking defects caused by a subset of these mutations can be corrected by sulfonylureas, KATP channel antagonists that have long been used to treat type 2 diabetes. More recently, carbamazepine, an anticonvulsant that is thought to target primarily voltage-gated sodium channels has been shown to correct KATP channel trafficking defects. This article reviews studies to date aimed at understanding the mechanisms by which mutations impair channel biogenesis and trafficking and the mechanisms by which pharmacological ligands overcome channel trafficking defects. Insight into channel structure-function relationship and therapeutic implications from these studies are discussed.